(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
In order to assist or restore the missing mobility, orthoses must be produced based on the specific anatomy and therapeutic needs of the particular patient. Powder-bed 3D printing technologies allow rapid and detailed manufacturing of complex structures. Application of powder-bed 3D printing technologies for orthopedic manufacturing makes it possible to produce lightweight, tailorable and reproducible rehabilitation devices. This promising manufacturing technique brings its uncertainties which must be answered before being used. Hence, it is very important to monitor the manufacturing quality and investigate the material behavior of the finished products.